PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pada Mebel Spring Bed Azkar) - Reni Indriani (Universitas Muhammadiyah Bengkulu, 2021)
ABSTRACKThis research was conducted at the furniture spring bed Azkar the city of Bengkulu. The title of this research is the Analysis of the effect of product quality on furniture customer satisfaction spring bed Azkar the city of Bengkulu. Population in this research is all customer ever Contribution of furniture the city of Bengkulu. Analysis of data used qualitatif analysis. The sample used in this research was 85 people. Data collection methods using observation, interview techniques and questionnaire. Based on this research’s result the owner of furniture Azkar have to keep and increase the quality from quality, price and model which is offered. The owner have to do it to make the customer satisfied and will come in future.